Liturgi Sebagai Perayaan Umat Menurut KHK Kanon 837: Upaya Mewujudkan Partisipasi Umat Dalam Kehidupan Sosial-Politik - Adon, Mathias Jebaru; Raharso, Alphonsus Tjatur (AL-ADYAN, 2022)
The involvement of Catholics in socio-political life in Indonesia is getting dimmer. The appreciation of the people's faith tends to be focused on inward fellowship, not outward. Whereas the call to become Catholics in Indonesia demands the active involvement of all communities as a contribution to the wealth of the nation's pluralism. This is influenced by the liturgical life which does not touch the struggles of daily life. The liturgy seems to return to Old Testament worship which distances people from celebrations, and worship seems to be a special business for the clergy. The true liturgy is a celebration of the entire community so that it becomes the source and peak of the Christian life. Therefore, this study aims to make the liturgy a celebration of all the people as stated in the Canon Law of the Catholic Church Canon 837. In this way, liturgical celebrations bring renewal of people's lives so that people are increasingly called to manifest their faith through their involvement in socio-political life in Indonesia. This research uses literature study from the perspective of phenomenology. This study found a link between the people's active participation in the liturgy and their involvement in community life.